A comprehensive review on time-honoured Chinese medicine brands of visual identity - Menguyao, Yu; Zainal Abidin, Sazrinee; Shaari, Nazlina (Human Resource Management Academic Research Society, 2023)
As the consumer demographic shifts towards a younger audience, the traditional visual identities of time-honoured Chinese medicine brands are facing challenges in keeping up with the evolving trends. To enhance consumer attitudes and perceptions, it has become imperative to rejuvenate the visual identities of these venerable brands. This study primarily aims to categorise the established time-honoured Chinese medicine brands along with their respective visual identities. By assessing the present status and significance of these historic brands, the research endeavours to investigate how key visual identity components such as symbols or logos, brand colours, typography, and brand names impact consumer attitudes. Through an in-depth exploration of these foundational visual identity elements, the study aspires to augment the consumers' positive brand perceptions towards time-honoured Chinese medicine brands. Moreover, the research aims to construct a comprehensive conceptual framework that not only contributes to the current understanding of consumer attitudes but also lays the groundwork for future research by offering valuable insights into these attitudes and related dimensions.